Vous êtes sur la page 1sur 3

x f(x) 1 0 1.5 1 2 2 2.5 −1.5
x f(x)
1 0
1.5 1
2 2
2.5 −1.5

f (x) {1, 1.5, 2, 2.5}

f (1.8)

x

f

f {x 0 , x 1 }

: [1, 1]

R p

x

x (x 2 )(x + 2 ) f : [1, 1] R

(x 1)(x + 1) x [1, 1]

, 1] → R ( x − 1)( x + 1) x ∈ [ − 1

2

1] → R ( x − 1)( x + 1) x ∈ [ − 1 ,

2

{x 0 , x 1 } {x 0 , x 1 } = {−1, 1} {x 0 , x 1 } = {− 2

2

{− 1 , 1 } { x 0 , x 1 } = {− √ 2

, 2

2

1 x

x 3 f

{− √ 2 , √ 2 2 2
{− √ 2
, √ 2
2
2

} x [1, 1]

}

{−1, 0, 1}

{− √ 2 , 0, √ 2 } 2 2
{− √ 2 ,
0, √ 2 }
2
2

{− √ 3 , 0, √ 3 } 2 2
{− √ 3 , 0, √ 3 }
2
2

n + 1 {x 0 ,

, x n } i

L i (x) =

n

j=0,j

=i

(x x j )

(x i x j )

n = 2 x 0 = 1, x 1 = 2, x 2 = 3 L i L

{x 0 ,

, x n } L

i

i

1

0

10

1.51 = 2

22

= 0

90

= 6

21

2.51

 

1.5

21

1 = 2

21.5

72

2.51.5 = 9

2

2

1.52

2.50.5 = 7

 
 

2.

1.5

{1, 1.5, 2, 2.5} 1, (x 1), (x 1)(x 1.5), (x 1)(x 1.5)(x 2) f {1, 1.5, 2, 2.5}

p(x) = 2(x 1) 6(x 1)(x 1.5)(x 2)

f (1.8) p f (1.8) p(1.8) = 1.888

[1, 1]

− 1)( x − 1 . 5)( x − 2) f (1 . 8) p f

[1, 1]

− 1)( x − 1 . 5)( x − 2) f (1 . 8) p f

{− 2

2

} p

f {x 0 , x 1 } f (x) p(x) ζ x

, x 1 } f ( x ) p ( x ) ζ x , √

, 2

2

e(x) = f (2) (ζ) (x x 0 )(x x 1 )

2

f (2) [1, 1] (x x 0 )(x x 1 ) [1, 1]

sup x[1,1] |(x x 0 )(x x 1 )| = 1

2

{x 0 , x 1 }

{− 2

= {− √ 2 , √ 2 2 2
= {− √ 2
, √ 2
2
2

} 1 {x 0 , x 1 } = {−1, 1}

2 2 2 } 1 { x 0 , x 1 } = {− 1 ,

2

, 2

2

}

p(x) = 1 2 x e(x) = 6ζ (x 2 )(x + 2 ) ζ [1, 1]

e(x) = x 3 1 2 x

ζ 0 |(x 2 )(x + 2 )|

ζ 0 | ( x − √ 2 )( x + √ 2 ) | 2

2

0 | ( x − √ 2 )( x + √ 2 ) | 2 2

2

2

0 | ( x − √ 2 )( x + √ 2 ) | 2 2

2

| ( x − √ 2 )( x + √ 2 ) | 2 2 2

2

1

2

|e(x) 6

2

× 1

2

= 3

2

{− 3 , 0, 3 } y = x(x 1)(x + 1)

, 0 , √ 3 } y = x ( x − 1)( x + 1)
, 0 , √ 3 } y = x ( x − 1)( x + 1)
, 0 , √ 3 } y = x ( x − 1)( x + 1)
2 2
2
2

y = x(x 2 )(x + 2 ) y = x(x 3 )(x + 3 )

2

2

2

2

sup x[1,1] |x(x− √ 3

2

)(x+ 3 )| < sup x[1,1] |x(x− √ 2 )(x+ 2 )| < sup x[1,1] |x(x1)(x+1)|

2

2

2

L 0 (x) =

L 1 (x) = (x 1)(x + 1) L 1 (x) = 2x + 1

L 2 (x) =

2 (x 2)(x 3) L 0 (x) = x 5

1

2

2 (x 1)(x 2) L 2 (x) = 1

1

2 x 3

2

L i (x) =

1

n

j=0,j

=i (x i x j )

n

n

k=0 j=0,j

=i,j

=k

(x x j )